The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/rsa.20292
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlation and log‐concavity

Abstract: (2009), 521-567); prove that "almost exchangeable" measures satisfy the "Feder-Mihail" property, thus providing a "non-obvious" example of a class of measures for which this important property can be shown to hold; and mention some further questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…The results in §6 are also useful in §7, as they allow us to show that the examples we construct there provide counterexamples to the series of conjectures on ultra log-concave rank sequences proposed in [65,72] to which we already alluded. We note that Corollary 6.6 in §6 was subsequently proved by different methods in [48], where it was additionally shown that almost exchangeable measures satisfy the (strong) Feder-Mihail property.…”
Section: (Nlc) µ(S)µ(t ) ≥ µ(S ∪ T )µ(S ∩ T ) For All S T ⊆ [N]mentioning
confidence: 80%
See 2 more Smart Citations
“…The results in §6 are also useful in §7, as they allow us to show that the examples we construct there provide counterexamples to the series of conjectures on ultra log-concave rank sequences proposed in [65,72] to which we already alluded. We note that Corollary 6.6 in §6 was subsequently proved by different methods in [48], where it was additionally shown that almost exchangeable measures satisfy the (strong) Feder-Mihail property.…”
Section: (Nlc) µ(S)µ(t ) ≥ µ(S ∪ T )µ(S ∩ T ) For All S T ⊆ [N]mentioning
confidence: 80%
“…In §7 we construct the first counterexamples in the literature to all of these conjectures except Mason's, which once again confirms the delicate nature of negative dependence. After this work was made publicly available on www.arxiv.org, other counterexamples to some of these conjectures were reported [48,60]. Markström [60] proved that negative association does not imply unimodality, and Kahn-Neiman [48] later showed that not even strong negative association (CNA+) implies unimodality.…”
Section: (Nlc) µ(S)µ(t ) ≥ µ(S ∪ T )µ(S ∩ T ) For All S T ⊆ [N]mentioning
confidence: 99%
See 1 more Smart Citation
“…Rayleigh measures were introduced in the context of matroid theory [38], but soon found their place in the modern theory of negative dependence for probability measures [23, 32]. The size‐increasing property can be viewed as a weak form of the so‐called normalized matching property, or as a strong form of the so‐called Feder–Mihail property (see [23] for definitions). Cavity‐monotone measures will play a major role in our study, for the following elementary reason.…”
Section: Introductionmentioning
confidence: 99%
“…† Very recently, counterexamples to the Big Conjecture have been found by Borcea, Brändén, and Liggett[4] and by Kahn and Neiman[26]. However, It is still reasonable to look for a hypothesis that excludes these examples and yet implies Mason's Conjecture for some restricted classes of matroids.…”
mentioning
confidence: 99%